Flow injection chemiluminescence determination of cefadroxil using potassium permanganate and formaldehyde system - Thongpoon C. (2014)
A simple, rapid and precise flow injection chemiluminescence (FI-CL) method is proposed for the determination of cefadroxil and is suitable for application to other antibiotics containing phenolic hydroxyl groups. A possible mechanism for this selectivity is suggested. The method is based on the CL-emitting reaction between cefadroxil and potassium permanganate in sulfuric acid medium, enhanced by formaldehyde (HCHO). Under the optimum conditions, calibration graphs over the ranges of 0.05-0.8 and 1.0-10.0 μg ml-1 were obtained. The proposed method was successfully applied to the determination of cefadroxil in pharmaceutical formulations with no evidence of interference from common excipients. The detection limit (3σ) of this method is 25 ng ml-1 (6.9 × 10-8 mol l-1). The relative standard deviation was less than 2% for 0.4 and 4.0 μg ml-1 cefadroxil (n = 20). The sample throughput was found to be 120 h-1. © 2006.